The Globalization of Science Curricula - Stacey, Oliver; De Lazzari, Giulia; Grayson, Hilary; Griffin, Hazel; Jones, Emily; Taylor, Amanda; Thomas, David (Cham Springer Nature, 2018)
Globalization; Science education; Science curricula; Large scale international assessments; Trends in International Mathematics and Science Survey; TIMSS; Policy borrowing; Curriculum reform; IEA Research for Education
English
Keywords: Education; Globalization; Science education; Science curricula; Large scale international assessments; Trends in International Mathematics and Science Survey; TIMSS; Policy borrowing; Curriculum reform; IEA Research for Education